Study on shock resistance of steel plate reinforced with polyurea–woven fiberglass mesh composite under shock wave. Issue 2 (June 2018) - Liao, Yu; Shi, Shaoqing; Liu, Zhaohui; Liang, Caoke
To study the dynamic mechanical properties of polyurea–woven fiberglass mesh composite material as a reinforcing layer, the shock resistance tests on plain steel plate, polyurea-reinforced steel plate, and polyurea–woven fiberglass mesh composite–reinforced steel plate were carried out using the large shock tube device. Finite element method simulation was also carried out. The results of experimental and numerical simulation show that the deformation of polyurea–woven fiberglass mesh composite reinforcing layer is smaller than that of pure polyurea reinforcing layer, and the overall deformation of steel plate reinforced by polyurea–woven fiberglass mesh composite is minimal among all the three specimens. With the same polyurea consumption in reinforcing layer, the mass of the 3.5-mm-thick polyurea–woven fiberglass mesh composite–reinforced steel plate is only 2.92% larger than that of the 3.2-mm-thick pure polyurea–reinforced steel plate, but it can reduce the residual displacement of steel plate center by additional 13.03%. The work in this article has some reference value to improve the shock resistance of polyurea-reinforced structure in engineering.